Adenoid cystic carcinoma: triple negative breast cancer with good prognosis. (3rd February 2016) - Romeira, Daniel; Cardoso, Débora; Miranda, Helena; Martins, Ana
Abstract : Adenoid cystic carcinoma of the breast (ACCb) is a rare type of breast cancer. The treatment is not consensual. The authors report two cases of ACCb. Case 1 : A 59-year-old woman with T1bN0M0, who went for lumpectomy and adjuvant radiation therapy (RT) (60 Gy in 30 fractions); Case 2 : A 43-year-old woman, who went for modified radical mastectomy with T3N1M0, and underwent adjuvant chemotherapy, and a sequential regimen with antracyclin and taxane, prior to adjuvant RT (50 Gy/25 fractions).